Turnover of Human Extrinsic (Tissue-Type) Plasminogen Activator in Rabbits - Korninger, C; Stassen, J M; Collen, D (Thrombosis and Haemostasis, 1981)
The turnover of highly purified human extrinsic plasminogen activator (EPA) (one- and two-chain form) was studied in rabbits. Following intravenous injection, EPA-activity declined rapidly. The disappearance rate of EPA from the plasma could adequately be described by a single exponential term with a t ½ of approximately 2 min for both the one-chain and two-chain forms of EPA.The clearance and organ distribution of EPA was studied by using 125I-labeled preparations. Following intravenous injection of 125I-1abeled EPA the radioactivity disappeared rapidly from the plasma also with a t ½ of approximately 2 min down to a level of 15 to 20 percent, followed by a small rise of blood radioactivity. Gel filtration of serial samples revealed that the secondary increase of the radioactivity was due to the reappearance of radioactive breakdown products in the blood. Measurement of the organ distribution of 125I at different time intervals revealed that EPA was rapidly accumulated in the liver, followed by a release of degradation products in the blood.Experimental hepatectomy markedly prolonged the half-life of EPA in the blood. Blocking the active site histidine of EPA had no effect on the half-life of EPA in blood nor on the gel filtration patterns of 125I in serial plasma samples.It is concluded that human EPA is rapidly removed from the blood of rabbits by clearance and degradation in the liver. Recognition by the liver does not require a functional active site in the enzyme. Neutralization in plasma by protease inhibitors does not represent a significant pathway of EPA inactivation in vivo.
Keywords: Extrinsic (tissue-type) plasminogen activator; Turnover in rabbits; Clearance mechanism; Inactivation